Chinese historical microdemography - Harrell, Stevan; Joint Committee on Chinese Studies (U.S.) (Berkeley : University of California Press, 1995)
Using local studies to answer global questions, this compilation challenges traditional notions concerning historical Chinese population trends. Genealogies, epitaphs, and household registers are some of the local and primary materials used to examine the important issues of fertility, mortality, family structure, and migration patterns.
Marriages among the Song elite / Patricia Ebrey -- Fertility and population growth in the lineages of Tongcheng County, 1520-1661 / Ted A. Telford -- Comparison of lineage populations in South China, ca. 1300-1900 / Liu Cuirong Demographic constraint and family structure in traditional Chinese lineages, ca. 1200-1900 / Liu Cuirong Marriage, mortality, and the developmental cycle in three Xiaoshan lineages / Stevan Harrell and Thomas W. Pullum -- Century of mortality in rural Liaoning, 1774-1873 / James Lee, Cameron Campbell, and Lawrence Anthony -- Migration in two Minnan lineages in the Ming and Qing periods / Wang Lianmao.
Papers from the conference sponsored by the Joint Committee on Chinese Studies.
Includes bibliographical references (pages 221-229) and index.
Print version record.
English.
JSTOR
Keywords: China -- Population; Families -- China -- History; Marriage -- China; China -- Social conditions -- 1644-1912.; Social history; Familles -- Chine -- Histoire; Mariage -- Chine; Chine -- Conditions sociales -- 1644-1912.; Histoire sociale; social history; SOCIAL SCIENCE -- Demography; SOCIAL SCIENCE / Demography; Families; Marriage; Population; Social conditions; China; Bevolking; China; 1644-1912; Demography; China; dissertations; History; Geschiedenis (vorm); Academic theses; Thèses et écrits académiques.